Analisa Nutrisi Pakan Ayam Kampung Berbahan Baku Jagung dan Dedak - Rizka Octavia; Nur Mu’min (Journal of Sustainable Research In Management of Agroindustry (SURIMI), 2023)
Local breed chicken is a type of chicken that is widely raised by rural communities. Local breed chicken feed is still limited to household food waste or left free to find food independently. Some are given additional feed in the form of corn or bran but without proper nutritional calculations. The right calculation on feeding will increase growth and the productivity of chickens. The additional feeds commonly used for the manufacture of local breed chicken feed are corn and rice bran which are available quite a lot and the prices are relatively cheap. The aim of this study was to determine the appropriate native chicken feed formulation. Five chicken feed formulations were made with the basic ingredients of corn and morning bran. The method used in this study was descriptive exploratory, the results of the feed formulation obtained from the research results were compared with SNI for broiler feed (SNI 01-3931-2006) and laying hens (SNI 01-3929-2006) because there was no standard feed for local breed chickens. village. The formulation results were tested for nutritional content including moisture, ash, protein, fat, and also crude fiber content. Based on the test results, it was found that the formulation of free-range chicken feed according to the SNI standards for broiler and layer chicken feed was the P2 formulation, with a ratio of 30 grams of corn and 24 grams of rice bran.